Community‐centred oral healthcare for adults experiencing homelessness in Australia: Perceptions and experiences of key stakeholders. (14th October 2022) - Durey, Angela; Lette, Helen; Saunders, Julie; Slack‐Smith, Linda
Abstract: The objective of the study was to identify whether creating a responsive, respectful and trustworthy environment that provides free dental care for clients who are homeless using volunteer dental professionals was effective in meeting their oral health needs in Fremantle, Western Australia. Qualitative research conducted between October 2018 and August 2019 was guided by a social constructivist paradigm to gather and analyse data. Semi‐structured interviews were conducted with adults experiencing homelessness accessing a community dental clinic and health providers and other stakeholders involved in its establishment, management and service delivery. An inductive approach to analysis was used to organise themes under the categories of 'establishing the oral health clinic' (OHC) and 'responses to the implementation of the clinic' Thirty‐nine semi‐structured interviews were conducted across eight participant groups: clients, executive management, the oral health clinical reference group, volunteer dentists, employed staff, nursing students, volunteer staff and other stakeholders. Key findings across all groups included positive responses to the establishment and implementation of the OHC, the quality of care and the safe and respectful environment in which services were delivered. Challenges related to sustainability include uncertainty around ongoing funding and recruitment of dental professionals. Whilst volunteer dental services fill a gap in meeting the complex needs of this population group, mainstream services must consider and address issues of equity in this context. Findings can be used to guide this process that includes creating environments of respect and trust where adults who are homeless or at risk of homelessness feel safe, welcomed and more likely to return to the service.